CRITICAL STUDY OF THE COMMERCIAL WISDOM OF COMMITTEE OF CREDITORS UNDER IBC - Viswajith T. S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Insolvency and Bankruptcy Code (IBC) of 2016, shaped by the Bankruptcy Law Reforms Committee, aims to create a structured, time-bound resolution framework for corporate insolvency in India. A key principle of the code is the role of the Committee of Creditors (CoC), empowered to make decisions based on commercial wisdom, which courts typically refrain from interfering with unless the decisions are irrational or unlawful. The CoC’s primary function is to protect creditors’ interests and maximize asset recovery, while balancing the rights of various stakeholders, including operational creditors. Judicial scrutiny of commercial wisdom has evolved through landmark judgments, emphasizing minimal intervention unless legal violations or bad faith are evident. Despite the code’s successes, challenges such as delays, recovery rates, and the exclusion of non-CoC creditors remain. The study suggests that while the CoC’s role is vital, there is a need to ensure inclusive decision-making and focus on corporate revival rather than liquidation. Ultimately, the IBC seeks to create an ecosystem that fosters business revival and value preservation, but its success depends on efficient, stakeholder-aligned practices.